No Effect of Anodal Transcranial Direct Current Stimulation Over the Motor Cortex on Response-Related ERPs during a Conflict Task - Conley, Alexander C.; Fulham, W. R.; Marquez, Jodie L.; Parsons, Mark W.; Karayanidis, Frini (Frontiers in Human Neuroscience, 2016)
Anodal transcranial direct current stimulation (tDCS) over the motor cortex is considered a potential treatment for motor rehabilitation following stroke and other neurological pathologies. However, both the context under which this stimulation is effective and the underlying mechanisms remain to be determined. In this study, we examined the mechanisms by which anodal tDCS may affect motor performance by recording event-related potentials (ERPs) during a cued go/nogo task after anodal tDCS over dominant M1 in young adults (Experiment 1) and both dominant and non-dominant M1 in old adults (Experiment 2). In both experiments, anodal tDCS had no effect on either response time or response-related ERPs, including the cue-locked contingent negative variation (CNV) and both target-locked and response-locked lateralised readiness potentials (LRP). Bayesian model selection analyses showed that, for all measures, the null effects model was stronger than a model including anodal tDCS vs. sham. We conclude that anodal tDCS has no effect on response time or response-related ERPs during a cued go/nogo task in either young or old adults.